Autophagy Dysfunction, Cellular Senescence, and Abnormal Immune-Inflammatory Responses in AMD: From Mechanisms to Therapeutic Potential. (22nd May 2019) - Wang, Shoubi; Wang, Xiaoran; Cheng, Yaqi; Ouyang, Weijie; Sang, Xuan; Liu, Jiahui; Su, Yaru; Liu, Ying; Li, Chaoyang; Yang, Liu; Jin, Lin; Wang, Zhichong
Abstract : Age-related macular degeneration (AMD) is a blinding disease caused by multiple factors and is the primary cause of vision loss in the elderly. The morbidity of AMD increases every year. Currently, there is no effective treatment option for AMD. Intravitreal injection of antivascular endothelial growth factor (anti-VEGF) is currently the most widely used therapy, but it only aims at neovascularization, which is an intermediate pathological phenomenon of wet AMD, not at the etiological treatment. Anti-VEGF therapy can only temporarily delay the degeneration process of wet AMD, and AMD is easy to relapse after drug withdrawal. Therefore, it is urgent to deepen our understanding of the pathophysiological processes underlying AMD and to identify integrated or new strategies for AMD prevention and treatment. Recent studies have found that autophagy dysfunction in retinal pigment epithelial (RPE) cells, cellular senescence, and abnormal immune-inflammatory responses play key roles in the pathogenesis of AMD. For many age-related diseases, the main focus is currently the clearing of senescent cells (SNCs) as an antiaging treatment, thereby delaying diseases. However, in AMD, there is no relevant antiaging application. This review will discuss the pathogenesis of AMD and how interactions among RPE autophagy dysfunction, cellular senescence, and abnormal immune-inflammatory responses are involved in AMD, and it will summarize the three antiaging strategies that have been developed, with the aim of providing important information for the integrated prevention and treatment of AMD and laying the ground work for the application of antiaging strategies in AMD treatment.